1984
DOI: 10.1039/f29848001529
|View full text |Cite
|
Sign up to set email alerts
|

Dark catalytic electron transfer in solid-state hydrogen-bonded electron-donor–electron-acceptor complexes

Abstract: The mechanism for the catalysis of electron-transfer reactions in systems with weak donor-acceptor properties has been considered. According to this mechanism, the reaction proceeds via the low-lying excited states of the complexes. These states are generated as a result of multiorbital bonds between the molecules of the reagents. The significant p?rt played by hydrogen and other bridge bonds in the stabilization of the excited levels of the complexes is shown. The energetic characteristics of complexation (ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…inherent to matter (both organic and inorganic) and occur at every place of the Universe wherever these compounds are located. In this connection, we are glad to note that our ideas of mechanisms of chemical reactions agree with the views of Oparin (1977) on the role of the electron and hydrogen transfer reactions in biochemistry; in addition, these ideas were formulated independently and approximately at the same time (Kalninsh 1981a(Kalninsh , 1984.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…inherent to matter (both organic and inorganic) and occur at every place of the Universe wherever these compounds are located. In this connection, we are glad to note that our ideas of mechanisms of chemical reactions agree with the views of Oparin (1977) on the role of the electron and hydrogen transfer reactions in biochemistry; in addition, these ideas were formulated independently and approximately at the same time (Kalninsh 1981a(Kalninsh , 1984.…”
supporting
confidence: 54%
“…At that time, no evidence was found in favour of proceeding chemical (biochemical) reactions via excited states of molecules and their complexes. Further development of the theory of chemical reactions was made in 1977 in our works (Kalninsh 1981a(Kalninsh , 1981b(Kalninsh , 1982(Kalninsh , 1984(Kalninsh , 1997. We have based our theory on completely different assumptions which were not related to biological systems, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Crystalline quinone3hydroquinone complexes (so-called quinhydrone) undergo redox transformations with an increase in the difference between the hydroquinone ionization potential and quinone electron affinity [10]. It has been shown that transfer of two hydrogen atoms from hydroquinone to quinone occurs in the electron-excited state of quinhydrone [11].…”
mentioning
confidence: 99%
“…The excited states of such complexes are responsible for the thermal transfer of the hydrogen atom [5], an elementary step of many organic reactions. The excited states of such complexes are responsible for the thermal transfer of the hydrogen atom [5], an elementary step of many organic reactions.…”
Section: Electron Donor3acceptor and Proton Donor3acceptor Propertiesmentioning
confidence: 99%